Comparison of [18F]AlF-NOTA-FAPI-04 PET/CT and [18F]FDG PET/CT for diagnosing lymph node metastasis in malignant tumors - Zhou, Wanjing; Dai, Jiashun; Zheng, Kai; Peng, Xiang; Zhang, Yanyin; Jiang, Chengzhi; Yang, Jian; Ye, Hui (Frontiers in Oncology, 2025)
PurposeThis study compared the diagnostic performance, semi-quantitative capability, and staging accuracy of [18F]AlF-NOTA-FAPI-04 and [18F]FDG PET/CT in detecting lymph node metastases.MethodsThis single-center retrospective study included 41 patients with suspected lymph node metastases who received both [18F]FDG and [18F]AlF-NOTA-FAPI-04 PET/CT. The study compared metastatic lymph node detection, semi-quantitative values, and N staging accuracy. Subgroup analyses were performed for lymph nodes with short-axis diameters (SADs) ≥10 and <10 mm.ResultsA total of 41 patients with 126 nodes were included. [18F]AlF-NOTA-FAPI-04 outperformed [18F]FDG in the detection of metastatic lymph nodes, achieving higher accuracy in both patient-based (92.7% vs. 70.7%, p = 0.004) and node-based analyses (91.3% vs. 60.3%, p < 0.001). In semi-quantitative analysis, the maximum standardized uptake value and target-to-background ratio of [18F]AlF-NOTA-FAPI-04 were higher than those of [18F]FDG in metastatic lymph nodes (all p < 0.001). Both tracers distinguished metastatic from benign nodes with SAD ≥ 10 mm (p < 0.05). [18F]AlF-NOTA-FAPI-04 PET/CT could distinguish between benign and metastatic lymph nodes with SAD < 10 mm (p < 0.001), whereas [18F]FDG PET/CT could not (p > 0.05). [18F]AlF-NOTA-FAPI-04 also provided more accurate N staging assessments (87.8% vs. 65.9%, p = 0.006). [18F]AlF-NOTA-FAPI-04 PET/CT enabled the correct diagnosis of more lymph nodes, leading to a change in the therapeutic regimen for eight patients (19.5%).Conclusion[18F]AlF-NOTA-FAPI-04 PET/CT demonstrated superior diagnostic performance, semi-quantitative capability, and N staging accuracy compared to [18F]FDG PET/CT, particularly for small metastatic lymph nodes (SAD < 10 mm), offering enhanced guidance for tumor staging.